Improving the EFL Learners’ Speaking Ability through Interactive Storytelling - Marzuki, Marzuki; Prayogo, Johannes Ananto; Wahyudi, Arwijati (Dinamika Ilmu: Jurnal Pendidikan, 2016)
This present research was aimed to improve the EFL learners’ speaking ability and their classroom activities through the implementation of Interactive Storytelling Strategy. Therefore, this study was directed to explore the beneficial of Interactive Storytelling that closely related to the EFL learners’ everyday activities at their home and school. The subject consisted of 22 of Junior High of Indonesian EFL learners. A Classroom Action Research in two cycles had been conducted within 6 meetings for every cycle. The meetings were focused on the interactivity and communicative ability among learners. The research result showed that the learners’ speaking ability improved from 17 or 72,27% passed in Cycle 1 to 22 or 100% passed the criteria of success in Cycle 2. It also showed that their classroom activities improved from 8 or 36,36% who were very active (VA) and 14 or 63,64% who were active (A) to 18 or 81,82% were very active (VA) and 4 or 18,18% were active (A). In conclusion, the implementation of Interactive Storytelling Strategy increased the EFL learners’ speaking ability and their classroom activities.